2002
DOI: 10.1053/eupc.2001.0204
|View full text |Cite
|
Sign up to set email alerts
|

PEA I and PEA II based implantable haemodynamic monitor: pre clinical studies in sheep

Abstract: The simultaneous recording of PEA I and PEA II with an implantable system offers a new chance to monitor indexes of LV systolic and diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 17 publications
1
45
0
Order By: Relevance
“…In particular, the peak to peak amplitude of first component of the EA signal (EA1) is well correlated to the maximum rate of rise of left ventricular pressure [8] and has been successfully used to optimize CRT [1].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the peak to peak amplitude of first component of the EA signal (EA1) is well correlated to the maximum rate of rise of left ventricular pressure [8] and has been successfully used to optimize CRT [1].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary experimental works have shown that the EA signal provides useful information about the inotropic state, showing that the peak-to-peak amplitude of the first EA component (EA1), which is synchronous with the first heart sound, is significantly correlated with the maximum derivative of the left ventricular pressure signal [2]. This amplitude has also been shown to decrease in humans during acute myocardial ischemia, where myocardial contractility is known to be decreased [3].…”
Section: Introductionmentioning
confidence: 99%
“…Four components can be identified during a single beat on the EA signal, corresponding to the four cardiac sounds on phonocardiography [2]: the closure of atrioventricular valves during the beginning of the systole (EA1), the closure of aortic and pulmonary valves (EA2), the end of the rapid filling of the ventricles (EA3) and the ventricular filling following the atrial contraction (EA4). In the sheep, the two last components were not distinguishable, and thus were grouped as component EA3/4.…”
Section: 3mentioning
confidence: 99%
“…30 PEA is strongly correlated with changes in LV and RV contractility (dP/dt max ) during inotrope infusion but not during pacinginduced chronotropic stimulation, 27,49 suggesting that monitoring PEA might serve as a useful surrogate for changes in myocardial contractility. Additionally, PEA sensors have also been used to guide device optimization in patients receiving CRT, and studies have suggested that AV and VV optimization using PEA may be equivalent to echocardiography-based algorithms 50 and LV dP/dt max algorithms.…”
Section: Other Sensor Modalitiesmentioning
confidence: 99%
“…However, most patients admitted for ADHF have pulmonary congestion caused by elevated left atrial pressure. 27 Therefore, continuous monitoring of left atrial pressure (LAP) may provide a more robust target for implantable sensor-based strategies. The HeartPOD (St Jude Medical Inc, Minneapolis, Minn) is a permanently implantable LAP sensor inserted during transseptal cardiac catheterization ( Figure 3).…”
Section: Hemodynamic Sensorsmentioning
confidence: 99%